The Delignification of Plants Residue Substrate and Accelerated Fungal Consortium Growth-Saccharification: A Practical Approach - Syauqi, Ahmad; Fatimah, Siti; Choiroh, Durrotul (International Journal of Renewable Energy Development, 2022)
The environments have created an abundance of residual plants from all life sectors, which is not optimal for bioethanol. Therefore, this research developed microbial technology that yielded sugar and fermentation testing. The research aimed to discover the delignification process and compare the consuming sugar by Saccharomyces cerevisiae between the chemical saccharification and accelerated bio-agent of fungal consortium in the engineered media. The innovation of the bioethanol process was conducted using raw materials from biomass. Based on this study, some preliminary hypotheses were made: (i) arranging fungal substrate which consists of residual sugar, molasses, and enriched residual papaya fruits could provide distinguishable growth of cell mass; (ii) the substrate concentration of 2.5% and 7.5% in the growth medium using enriched residual papaya fruits, respectively, as a medium, could be distinguished using delignification. A benchmark was used to compare the chemical and bio-agent saccharification. The consortium that grew and produced cell mass by times factor in molasses has fulfilled the element needed compared to the natural organic substances from the papaya fruit. The higher concentration of delignification material substrate yielded higher growth-saccharification and the average of 10.45 Â± 0.21 % Brix was obtained by the fungal consortium in the broth medium, although the acceleration growth is insignificant. Nonetheless, Saccharomyces cerevisiae had successfully fermented saccharification yield sugar from the delignification of plants residual